Moscow sting - Alex Dryden (UK Headline Publishing Group, 2009)
The threat of Russia as a hostile superpower returns in this chilling spy thriller.When British spy, Finn, is brutally murdered by a Russian assassin, Adrian, chief of MI6, wants vengeance. He also wants answers - answers that can only be revealed by Finn's widow, Anna, the former KGB colonel who betrayed her country for love and has now disappeared with their child. Adrian isn't the only one desperate to find Anna. Finn accessed intelligence so confidential that the KGB are willing to kill to protect it, and now everyone wants to know what Russia is concealing beneath its veil of political cordiality.Booklist places author Alex Dryden in (3z(Bthe top rank of espionage novelists.(3y (BHis riveting Moscow Sting proves that the resounding critical acclaim awarded him for his debut, Red to Black, was no fluke. In this spellbinding sequel, former KGB colonel Anna Resnikov escapes to America where she must outwit CIA (3z(Bfriend(3y (Band KGB foe alike to survive. Alex Dryden has brought breathtaking new life to the spy novel in this blistering (3z(Bripped from the headlines(3y (Bthriller that focuses on Russia$1 (Bs chilling reemergence as a hostile superpower.s
Keywords: English Literature